Portraits and self-portraits of composers at the musical work - Serhaniuk, Liubov; Shapovalova, Liudmyla; Shehda, Lidiia; Kazymyriv, Khrystyna; Kolubayev, Oleg (MAGNANIMITAS Assn., 2021)
The purpose of this exploration is to reveal the means and methods of artistic self-identification of the composer, recognizability of the uniqueness of his figure through a set of semantically expressive and symbolic features of individual style in the genres of musical portrait and self-portrait of the composer. In this regard, the need to take into account important methodological adjustments to the use of musical thinking as a complex syncretic category was actualized, because, in the study of portraiture samples, not only stylistic properties of musical text are important, but also mechanisms to cover the prototype in the integrity of visual, cultural, and stylistic embodiments and formation of a musical image on this basis. From this investigation, the following conclusions follow: a comprehensive consideration of methods of depicting the recognizable image of a particular musician-creator (personified bearer of absolute creativity) in a musical work in three versions - introverted (selfidentification, self-reflection, confession, self-analysis) representative (image, image, style, cartoon), and symbolic (signature, cryptogram, puzzle, generalization through style and genre, quote, etc.). The reference to quoting the monograms of outstanding musicians testifies to the desire of artists of other epochs to comprehend the artistic value and scale of their contribution to world music, to single out semantic dominants, in particular in polyphonic genres.
Keywords: Композиторська творчість, композиторський стиль, музичний портрет, музична творчість